Comparison of mechanical and tribotechnical properties of UHMWPE reinforced with basalt fibers and particles; IOP Conference Series: Materials Science and Engineering; Vol. 156 : Materials and Technologies of New Generations in Modern Materials Science - Panin S. V. Sergey Viktorovich; Kornienko L. A.; Aleksenko V. O. Vladislav Olegovich; Huang Qitao; Ivanova L. R. (2016, 2016)
Title screen